Inflation, population and economic growth : Co - integration and causality analysis of Malaysia / Noor Faziedah Chun Lee @ Mohd Fadzlee - Chun Lee @ Mohd Fadzlee, Noor Faziedah (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2012)
This paper focus on the study of macroeconomics variables that are inflation, population and economic growth. The main objective is to identify and examined the economic factors that affected economic growth. In this study, data was including in time series data from year 1981 until 2010 that involved around 30 years. The data including three variables that are economic growth, inflation and population. The effect of inflation on economic growth and how population relates to inflation. The stationary properties of the time series data are examined by using Augmented Dickey-Fuller (ADF) and Phillips- Perron (PP). To find out long-run relationship along the variables, this paper using the Econometrics Technique, Johansen Maximum Likelihood Co-integration. Granger Causality tests is applied in this paper to find out the causality among the three variables. Based on findings from the co-integration test. It is shows that there is long run relationship exists among inflation, population and economic growth. There is also causality between inflation to population and economic growth to inflation but there is no causal relation between population and economic growth. From VECM test, we can found that there is short run relation between economic growth and population.